The Development of International Criminal Justice: Expectations and Reality - Gutnyk, Vitalii (Teisė, 2023)
The article deals with the efficiency of international criminal justice. It is proved that the development of the system of international criminal justice took place rather in waves, and the permanent International Criminal Court can hardly be called an effective judicial institution. All international criminal courts encountered the same problems and were effective if there was adequate cooperation between the states. Attention is drawn to the existing armed conflict in Ukraine and the prospects of prosecution of persons who committed international crimes.